2014
DOI: 10.1103/physrevb.89.024503
|View full text |Cite
|
Sign up to set email alerts
|

Kondo-like mass enhancement of Dirac fermions in Ba(Fe1xMnxAs)2

Abstract: The effect of Mn substitution, acting as a magnetic impurity for Fe, on the Dirac cone was investigated in Ba(Fe1−xMnxAs)2. Both magnetoresistance and Hall resistivity studies clearly indicate that the cyclotron effective mass (m * ) of the Dirac cone is anomalously enhanced at low temperatures by the impurity, although its evolution as a function of carrier number proceeds in a conventional manner at higher temperatures. Kondo-like band renormalization induced by the magnetic impurity scattering is suggested … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…This is in agreement with previous experimental observations on Mn substituted pnictides. [16][17][18][19]27 The temperature dependence of the shape of the 75 As-NQR spectra was checked for some representative samples (x = 0.025 % and x = 0.075 %). The results are plotted in Fig.…”
Section: Technical Aspects and Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with previous experimental observations on Mn substituted pnictides. [16][17][18][19]27 The temperature dependence of the shape of the 75 As-NQR spectra was checked for some representative samples (x = 0.025 % and x = 0.075 %). The results are plotted in Fig.…”
Section: Technical Aspects and Experimental Resultsmentioning
confidence: 99%
“…15 Several experimental techniques such as nuclear magnetic resonance (NMR), inelastic neutron scattering and photoemission spectroscopy showed that no charge doping occurs upon Mn substitution and that Mn moments tend to localize, suggesting that the moments are acting as magnetic scattering centers. [16][17][18][19] Also in undoped (antiferromagnetic) LaFeAsO, Mn magnetic moments affect the long range magnetic order within the Fe planes, which evolves into a short range magnetic order upon adding Mn, without leading to the onset of superconductivity. 20 Here we focus on the peculiar case of Mn substituion on the Fe site in nominally optimally doped LaFeAsO 0.89 F 0.11 .…”
mentioning
confidence: 99%
“…Rich physics in the transport properties of iron pnictide (FePn) materials is the consequence of the complex d-orbital energy bands with unique topology [1,2], and the unconventional high temperature superconductivity [3] and the intriguing quantum transport phenomena resulting from Dirac cones forming via spin density wave (SDW) band folding [4][5][6][7][8][9] have been reported so far. Despite various experimental observations as well as theoretical calculations, debate continues in understanding the real band picture of FePns.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that the spin-orbit interaction on iron is rather weak compared to Bi-based p -band TIs might look as if these two systems belonged to a different material class. However, a perusal of extant experimental567891011 and theoretical121314 studies suggests band topology with Dirac cones15 in iron-based superconductors. The Dirac cone band dispersions in iron-based superconductors are normally absent in the non-magnetic phase, but surprisingly they appear in the magnetically ordered state912.…”
mentioning
confidence: 99%
“…In this work we provide new insights to the problem of multi-orbital (MO) electron-electron interactions in tetragonal FeS, revealing the emergence of an orbital-blocked phase46 with linear spectrum and its possible implications for Kondo-like mass enhancement of Dirac fermions in iron-based superconductors8.…”
mentioning
confidence: 99%